2015
DOI: 10.1089/vbz.2014.1759
|View full text |Cite
|
Sign up to set email alerts
|

Converting Mosquito Surveillance to Arbovirus Surveillance with Honey-Baited Nucleic Acid Preservation Cards

Abstract: Spatially and temporally accurate information about infectious mosquito distribution allows for pre-emptive public health interventions that can reduce the burden of mosquito-borne infections on human populations. However, the labile nature of arboviruses, the low prevalence of infection in mosquitoes, the expensive labor costs for mosquito identification and sorting, and the specialized equipment required for arbovirus testing can obstruct arbovirus surveillance efforts. The recently developed techniques of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 26 publications
3
52
0
Order By: Relevance
“…This finding is supported by studies across Australia which have found that RRV infection rates (human and mosquito) vary at a relatively small scale [4,[35][36][37]. The fine-scale variation in disease rates we see here could be due to variation in reporting/testing by medical practitioners, behavioural differences of the patients or could represent variation in transmission ecology [19,34]; potentially all three factors are influencing disease rates to some degree. The fine-scale variation in disease rates we see here could be due to variation in reporting/testing by medical practitioners, behavioural differences of the patients or could represent variation in transmission ecology [19,34]; potentially all three factors are influencing disease rates to some degree.…”
Section: Using Landscan To Improve Map Interpretationsupporting
confidence: 82%
“…This finding is supported by studies across Australia which have found that RRV infection rates (human and mosquito) vary at a relatively small scale [4,[35][36][37]. The fine-scale variation in disease rates we see here could be due to variation in reporting/testing by medical practitioners, behavioural differences of the patients or could represent variation in transmission ecology [19,34]; potentially all three factors are influencing disease rates to some degree. The fine-scale variation in disease rates we see here could be due to variation in reporting/testing by medical practitioners, behavioural differences of the patients or could represent variation in transmission ecology [19,34]; potentially all three factors are influencing disease rates to some degree.…”
Section: Using Landscan To Improve Map Interpretationsupporting
confidence: 82%
“…Plant samples were assessed in 31.9% of the included articles, and samples obtained from insects corresponded to 14.9%. These works aimed to amplify viral RNA of arboviruses that can cause disease in humans, and also viruses capable of causing disease in fishes and plants (Hall-Mendelin et al, 2010;Price et al, 2014;Flies et al, 2015;Yang et al, 2015;Navaneeth Krishnan et al, 2016;Hall-Mendelin et al, 2017;Melanson et al, 2017;Chikh-Ali et al, 2016). Viral specimens were derived from cell culture or from a commercial inactivated vaccine in 10.6% of the reports (Muthukrishnan et al, 2008;Li et al, 2012;Bankamp et al, 2013;Sakai et al, 2015;Montmayeur et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This challenge is particularly relevant in settings where proper technical support for RNA handling may not be available (hereafter referred to as fieldwork). Although some studies have evaluated the FTA® cards for viral RNA preservation (Ndunguru et al, 2005;Muthukrishnan et al, 2008;Flies et al, 2015), the optimal conditions for their handling have not been extensively studied. Notwithstanding, it is crucial to determine the appropriate temperature and maximum time for storing RNA samples on FTA cards, as well as their biosafety, in order to fieldwork with these pathogens.…”
mentioning
confidence: 99%
“…We found that after 11 dpi, most samples were negative for ZIKV (apart from one positive salivary gland of A. aegypti given 10 To confirm that the virus detected in the salivary glands by RT-qPCR was being released in saliva during consecutive blood meals, we followed up the viral load from days 8 to 14 postinfection using filter paper cards. This strategy of viral RNA detection directly from FTA cards has been employed in previous studies for arbovirus surveillance (16,17). In the present study, we successfully detected ZIKV RNA copies in cards from A. aegypti and C.…”
Section: Discussionmentioning
confidence: 64%